Molecular identification and probiotic potential characterization of lactic acid bacteria isolated from the pigs with superior immune responses - Ma, Wenjie; Zhang, Wenli; Wang, Xinrong; Pan, Yu; Wang, Mengjie; Xu, Yunfei; Gao, Junxin; Cui, Hongyu; Li, Changwen; Chen, Hongyan; Zhang, He; Xia, Changyou; et al. (Frontiers in Microbiology, 2024)
Lactic acid bacteria (LAB) belong to a significant group of probiotic bacteria that provide hosts with considerable health benefits. Our previous study showed that pigs with abundant LAB had more robust immune responses in a vaccination experiment. In this study, 52 isolate strains were isolated from the pigs with superior immune responses. Out of these, 14 strains with higher antibacterial efficacy were chosen. We then assessed the probiotic features of the 14 LAB strains, including such as autoaggregation, coaggregation, acid resistance, bile salt resistance, and adhesion capability, as well as safety aspects such as antibiotic resistance, hemolytic activity, and the presence or absence of virulence factors. We also compared these properties with those of an opportunistic pathogen EB1 and two commercial probiotics (cLA and cLP). The results showed that most LAB isolates exhibited higher abilities of aggregation, acid and bile salt resistance, adhesion, and antibacterial activity than the two commercial probiotics. Out of the 14 strains, only LS1 and LS9 carried virulence genes and none had hemolytic activity. We selected three LAB strains (LA6, LR6 and LJ1) with superior probiotic properties and LS9 with a virulence gene for testing their safety in vivo. Strains EB1, cLA and cLP were also included as control bacteria. The results demonstrated that mice treated LAB did not exhibit any adverse effects on weight gain, organ index, blood immune cells, and ileum morphology, except for those treated with LS9 and EB1. Moreover, the antimicrobial effect of LR6 and LA6 strains was examined in vivo. The results indicated that these strains could mitigate the inflammatory response, reduce bacterial translocation, and alleviate liver, spleen, and ileum injury caused by Salmonella typhimurium infection. In addition, the LR6 treatment group showed better outcomes than the LA6 treatment group; treatment with LR6 substantially reduced the mortality rate in mice. The study results provide evidence of the probiotic properties of the LAB isolates, in particular LR6, and suggest that oral administration of LR6 could have valuable health-promoting benefits.